Efektivitas Model Pembelajaran Think, Pair, and Share Berbantuan Power Point Terhadap Keterampilan Membaca: Studi Eksperimen di SD Islam Panglima Besar Soedirman Jakarta Timur - Hartoko, Farah Ananda; Ridlo, Ubaid; Raswan, Raswan (Kopertais Wilayah I DKI Jakarta dan Banten, 2025)
The lack of students’ interest in reading Arabic texts is often caused by the use of conventional teaching models, such as the lecture method, which tends to be monotonous and hampers comprehension. In addition, some students still struggle with reading Arabic texts, preventing them from achieving the learning objectives effectively. This study aims to examine the effectiveness of the Think, Pair, and Share learning model in improving students' Arabic reading skills. This research employs a quantitative method with an experimental approach using the Nonequivalent Control Group Design. The research subjects consisted of 38 fifth-grade students, divided into an experimental group (19 students) and a control group (19 students). Data collection techniques included tests, interviews, and observations, while data analysis was conducted using the Shapiro-Wilk test, homogeneity test, independent sample T-test, and N-Gain test. The results indicate that the Think, Pair, and Share model, assisted by PowerPoint, is effective in enhancing Arabic reading skills. The post-test average score of the experimental group reached 80, higher than the control group, which scored 74.73. The independent sample T-test results showed a sig. (2-tailed) value of 0.004 (< 0.05), indicating a significant difference between the two groups. Additionally, the N-Gain test result of 0.4 demonstrates that the effectiveness of the learning model falls within the moderate category. Thus, the Think, Pair, and Share model is proven to have a positive impact on improving students' Arabic reading skills.